INCREASING THE EFFECTIVENESS OF EDUCATION OF STUDENTS IN THE SPIRIT OF DEVOTION TO THE MOTHERLAND AND PATRIOTISM (International journal of artificial intelligence, 2026)
This article is about increasing the effectiveness of educating students in a patriotic spirit.